HIDROLISIS LIGNOSELULOSA PELEPAH DAN TANDAN KOSONG KELAPA SAWIT DENGAN KATALIS ZIRKONIA TERSULFATASI - Anis Kristiani; Kiky Corneliasari Sembiring; Haznan Abimanyu; Fauzan Aulia (Jurnal Kimia Terapan Indonesia, 2013)
Lignocellulosic biomass which are frond and empty fruit bunches (EFB) is second generation raw material for ethanol production. Lignocellulose usage is expected to create a green process. Utilization of lignocellulose materials into ethanol involved four main processes, i.e pretreatment, hydrolysis/sacharification, fermentation, distillation and dehydration ethanol that was product. This research aims to optimize hydrolysis process of EFB and frond by using sulfated zirconia catalyst characterized its physical and chemical properties as a solid acid catalyst. Catalytic hydrolysis process conducted at 160 DCfor 3 hours gave the highest TRS (Total Reducing Sugar) which is 17,51 % for EFB while for frondfor 2 hours which is 19,23 % .Keyword: Hydrolysis, solid acid catalyst, lignocellulose, frond, EFB, sulfated zirconia